Find the general solution of xy3dx+ex2dy=0

Sagot :

Answer:

ln(x) - e/(2y^2) = constant; in other words, y = 1 / (√(2ln(kx)) )

Step-by1-step explanation:

divide the expression xy^3dx+ex^2dy=0 by (x^2) x (y^3).

we get, dx/x + edy/y^3 = 0

Integrating , ∫(1/x)dx + ∫e(1/y^3)dy , we get

= > ln(x) + ey^(-2)/(-2) = constant

= >  ln(x) - e/(2y^2) = constant

= > e/(2y^2) = ln(x) - d       (where d is a constant)

Let d = ln(k)          (where k is a constant too)

= > e/(2y^2) = ln(x) - ln(k) = ln(x/k)

2y^2 = 1/ln(x/k)

y = 1 / (√(2ln(cx)) )      (where c = 1/k)